EXPLORING MULTILINGUAL INTERACTION STRATEGIES FOR DISTANCE LEARNING SCENARIOS - Pedro Willging (PUPIL: International Journal of Teaching, Education and Learning, 2026)
We explored a couple of artificial intelligence apps for automatic translation in virtual environments. The objective of our research was to test the current capabilities of these tools for effective communication among people who speak different languages in virtual meetings. Participants in Argentina were making a slide presentation speaking in Spanish to a US audience. The US group was made up of English speakers (without knowledge of Spanish) and also two bilingual participants who acted as monitors of the experience. The AI apps made transcriptions during the synchronous online session, and replicated the voice interactions through dubbing. In our learning experiment, we found that the technological tools we evaluated were good enough to present content and discuss it in a quite fluent way between participants speaking different languages. We plan to keep looking for tools that enable efficient interactions between people in multicultural teams.